Effects of Temperature and Heating Time on Degradation and Antioxidant Activity of Anthocyanin from Roselle Petals (Hibiscus sabdariffa L.) - Suzery, Meiny; Nudin, Burhan; Nurwahyu Bima, Damar; Cahyono, Bambang (International Journal of Science, Technology & Management, 2020)
The effects of temperature and heating time on the degradation and antioxidant activity of anthocyanin compounds from roselle petals (Hibiscus sabdariffa L.) have been evaluated from this research. The purpose of this study is to determine, the degradation and antioxidant activity of anthocyanin compounds on variations of temperature and heating time. In this study anthocyanin was extracted from roselle petals using ethanol solvent at 25oC. Then the anthocyanin extract obtained was dissolved into aqueous solution. The solution was then heated at 40oC, 60oC and 80oC for 60 minutes. The degradation of anthocyanin compounds was analyzed by calculating the total of anthocyanin contents, while the antioxidant activity was evaluated using the DPPH method. The results showed that Total Anthocyanin Content (TAC) from the extract solution before heating was 144.28 mg/L. Meanwhile the total value of anthocyanin in the 60 minutes after heating at 400C, 600C and 800C are 108.88 mg/L, 88.84 mg/L and 63.78 mg/L respectively. Heating at 80oC decreases antioxidant activity by increasing the IC50 value to 86.8 ppm higher than the conditions before heating. The increase of temperature and length of the heating process made the anthocyanin structure degraded. Degradation was indicated by the reduction of total anthocyanin content and the decrease of antioxidant activity.